The Microstructures of Tetradesmus obliquus Biofilms Formed Under Different Nutrient Supplies - Hu Zhang; Guan Chen; Zhiying Sun; Xinru Zhang; Zeyi Jiang; Xinxin Zhang (Applied Sciences)
The microstructures of microalgae biofilms affect biofilms’ growth, which is critical in developing efficient microalgae biofilm-based culture systems. Herein, the microstructures of Tetradesmus obliquus biofilms cultured under different nutrients were in situ observed with confocal laser scanning microscopes. The surface structures and internal pore structures for these biofilms were determined quantitatively. The results indicated that the surfaces of these biofilms were all wrinkled with many folds in micrometres. The biofilms cultured under BG11, BG11+glycerine, BG11+urea, and BG11+NH4Cl nutrients had small pores with diameters of 15~30 μm, whereas the biofilms formed under BG11+NaHCO3 and BG11+NaNO3 presented many large pores with diameters of 50~150 μm. The mechanism of forming different microstructures of these nutrients was interpreted by analyzing cell surface properties. We found that the cells cultured under BG11+NaHCO3 and BG11+NaNO3 had more hydrophobic surface groups. The high cell–cell interactions between hydrophobic cells made cells tend to aggregate together and form biofilms with more inner pores, which may be conducive to cell growth and biofilm development. The study offers new insights into understanding the microstructural characteristics of microalgae biofilms cultured under different nutrients, providing important guidance for the development of biofilm-based culture systems.